A Catalogue of the Muscidae (Diptera) of the Neotropical Region - de Carvalho, C. J.b.; Couri, M. S.; Pont, A. C.; Pamplona, D.; Lopes, S. M. (Zootaxa, 2005)
The Muscidae (Diptera) of the Neotropical Region are catalogued. 843 extant and 3 extinct species in 84 genera are listed together with their synonyms, giving a total of 1209 names. References are given to the original descriptions and the subsequent taxonomic, biological and applied literature, the location of types, and the geographic distribution. A comprehensive bibliography is provided. There are one new specific synonym, one new generic synonym, 15 new combinations, one new specific name, two new generic names, and one re-instated name (with a second one that is accepted here but is being formally re-instated in a paper listed as "in press").